2002
DOI: 10.1515/cclm.2002.088
|View full text |Cite
|
Sign up to set email alerts
|

High-dose Methylprednisolone Therapy in Multiple Sclerosis Increases Serum Uric Acid Levels

Abstract: Uric acid, which is the final product of purine nucleoside metabolism, is a strong peroxynitrite scavenger. Several studies report on lower serum uric acid levels in multiple sclerosis. In this study, we investigated serum uric acid levels before and after high-dose methylprednisolone treatment (intravenous 1 g/day/5 days) in multiple sclerosis patients. Blood samples from 25 definite multiple sclerosis patients (11 male and 14 female) before and after methylprednisolone treatment (days 0, 6 and 30) and from 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 32 publications
1
12
0
2
Order By: Relevance
“…This study favored the view that reduced UA in MS acts as a primary, constitutive loss of protection against oxidative agents. This reduction has been confirmed in other studies that showed also an inverse correlation with clinical and neuroradiological disease activity [11], while therapy with steroid boli for clinical relapses was associated with a significant increase in the values of UA compared to pre-treatment values [12].…”
Section: Introductionsupporting
confidence: 75%
“…This study favored the view that reduced UA in MS acts as a primary, constitutive loss of protection against oxidative agents. This reduction has been confirmed in other studies that showed also an inverse correlation with clinical and neuroradiological disease activity [11], while therapy with steroid boli for clinical relapses was associated with a significant increase in the values of UA compared to pre-treatment values [12].…”
Section: Introductionsupporting
confidence: 75%
“…In addition, the administration of high-dose methylprednisolone for the treatment of MS relapse resulted in an increase in serum UA concentrations in the study by Toncev et al (40).…”
Section: Discussionmentioning
confidence: 93%
“…Consequently, treatment attempts in human MS with a precursor of uric acid have been reported (26,27). A few studies have demonstrated elevated serum uric acid levels after the administration of some drugs, such as glatiramer acetate (28) and high-dose methylprednisolone (29), indicating that some beneficial effects of these drugs might be due to the elevation of serum uric acid levels.…”
Section: Discussionmentioning
confidence: 99%